Incidencia de la Producción de Aguacate Hass del Municipio de Fresno en el Departamento del Tolima 2007-2021 y la Oferta Exportable de Aguacate Hass del Departamento del Tolima en el Mercado Internacional Entre los Años 2017-2020 (2024)
This study analyzes the influence of Hass avocado production in Fresno town on the GDP of Tolima between 2007 and 2021 through an econometric model. The results reveal a significant impact supported by a constant of 11,158.0 and a coefficient of 0.213446, both statistically significant. The constant represents the expected GDP when avocado production is zero, and the coefficient indicates the projected change in GDP per unit change in avocado production.